Disease-free survival after robotic-assisted laparoscopic total pelvic exenteration for recurrent cervical adenocarcinoma: A case report. Issue 30 (July 2018) - Yang, Qiyu; Tang, Junying; Xiao, Lin
Abstract: Rationale: Pelvic exenteration is considered a method to treat central recurrent or persistent gynecologic malignancy after the initial therapy. The postoperative survival rate has been greatly increased by the improvement in the surgical technology and the perioperative management. Yet various complications are still impacting the quality of life. New technologies such as robotic surgery system made it possible to approach radical surgical resection by using a minimally invasive method. Patient concerns: The patient is a 53-year-old female with the cervical adenocarcinoma pelvic recurrence who had undergone the adjuvant chemo-radiotherapy and the laparoscopic radical hysterectomy in our hospital 2 years ago. She still expected her life to be prolonged through surgery therapy. Diagnoses: Locoregional recurrence of cervical adenocarcinoma. Interventions: A robotic total pelvic exenteration with ileal neobladder was performed. Outcomes: The postoperative results were excellent and after 17-month follow-up, the patient is alive and satisfied without any recurrence or distant metastasis. Lessons: For the patients with advanced or recurrent cervical cancer who are willing to receive surgical therapy and not sensitive to chemo-radiotherapy, robotic-assisted laparoscopic total pelvic exenteration is technically a feasible surgical method for recurrent pelvic malignancies. Yet the operation time should be further controlled to reduce complications which include pressure sore and thrombus. Moreover, appropriate assessment is required in the selection of the methods for reconstruction.